EUPHEMISMS AS A MEANS OF MANIPULATION IN PEDAGOGICAL DISCOURSE - Katermina, Veronika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Nowadays a language presents a great interest not only as an independent phenomenon but also as a means of communication. In the course of a verbal communication between interlocutors there is an exchange of information as well as a manipulative influence. The latter is one of the main elements of an effective educational process.Euphemism is a mild or indirect word or expression substituted for one considered to be too harsh or blunt when referring to something unpleasant. It is the act or an example of substituting a mild, indirect, or vague term for one considered harsh, blunt, or offensive. Euphemisms with communicative function of evasiveness, politeness, and concealing, play dual parts in everyday social lives.Euphemism, a kind of polite language, can combine the teachers’ role and the students’ personalityfactors together. A verbal manipulation made by a teacher-manipulator with the help of euphemisms promotes improvement and an effective transformation of all the components moving an educational process forward. It regulates a positive interpersonal communication between a teacher and a student as well as within the class; it influences the work with the educational material and its further presentation; it creates a favourable working atmosphere during the lesson.